2022
DOI: 10.26418/jppk.v11i6.55120
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Antara Minat Dan Keaktifan Siswa Dengan Hasil Belajar Pada Pembelajaran Tematik Kelas Iii

Abstract: This study aims to describe the correlation between student interest and activity with learning outcomes in thematic learning in class III SDN 16 Pontianak City. The method used is a descriptive method with a quantitative approach. The population and sample in this study were all students of class IIIA, amounting to 22 students. Data collection techniques in this study are direct observation techniques, indirect observations and documentary studies. The data collection instruments used were questionnaires and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Hasil belajar adalah kemampuan-kemampuan yang dimiliki murid setelah ia menerima pengalaman belajarnya (Sudjana, 2009). Hal senada dikemukakan oleh Mulyono mengatakan bahwa hasil belajar adalah kemampuan yang diperoleh anak setelah melakukan suatu kegiatan belajar (Mulyono, 2003;Herbiadi, 2012;Susisusanti dkk, 2021). Kemampuan yang diperoleh adalah hasil yang dicapai dalam bentuk angka-angka atau skor setelah diberikan tes hasil belajar setiap akhir pembelajaran.…”
Section: Belajar Dan Hasil Belajarunclassified
“…Hasil belajar adalah kemampuan-kemampuan yang dimiliki murid setelah ia menerima pengalaman belajarnya (Sudjana, 2009). Hal senada dikemukakan oleh Mulyono mengatakan bahwa hasil belajar adalah kemampuan yang diperoleh anak setelah melakukan suatu kegiatan belajar (Mulyono, 2003;Herbiadi, 2012;Susisusanti dkk, 2021). Kemampuan yang diperoleh adalah hasil yang dicapai dalam bentuk angka-angka atau skor setelah diberikan tes hasil belajar setiap akhir pembelajaran.…”
Section: Belajar Dan Hasil Belajarunclassified
“…Artinya, semakin baik penerapan pendekatan konstruktivisme maka semakin baik pula hasil belajar mahasiswa, begitu sebaliknya semakin kurang baik penerapan pendekatan konstruktivisme, semakin menurun pula hasil belajar mahasiswa. Sejalan dengan penelitian Jasumayanti, terdapat korelasi yang siginifikan antara penerapan pendekatan konstruktivisme dengan hasil belajar siswa dalam pembelajaran IPS kelas IV Sekolah Dasar Negeri 35 Pontianak Selatan (Jasumayanti & Marli, 2013).…”
Section: Hasil Dan Pembahasanunclassified
“…High interest in reading is the basis for student success in various ways, especially in learning outcomes. With an interest in reading, students will gain knowledge from those who previously did not know to know, gain broad insights, and increase knowledge so that it will affect their learning outcomes (Harlika et al, 2019). It can be concluded that interest in reading has a positive relationship with improving students' reading comprehension skills.…”
Section: Introductionmentioning
confidence: 99%